The influence of demonstrative learning methods against gross motor skills of early childhood - Hidayat, Rezha Arzhan; Faizah, Khairani (Jorpres (Jurnal Olahraga Prestasi), 2023)
The purpose of this study was to evaluate the effect of demonstrative learning methods on improving gross motor skills in early childhood and provide pedagogical recommendations for the development of effective learning approaches. Through an in-depth literature review, this article reveals the complexity of the interaction between exercise activities and the changes in body physiology that occur. This research uses a qualitative descriptive research model that is a literature study that uses various literature reviews in strengthening research analysis. This research began by collecting some literature, then conducted a review and the collected literature was analyzed with a critical Apprasial table of 10 literature. In the literature review on the effect of demonstrative learning methods on early childhood gross motor skills, many studies support the effectiveness of these methods by emphasizing the use of models, simulations, and demonstrations. Despite variations in research results, the literature provides a strong basis for continued research to explore optimal implementation strategies to enhance the positive impact of demonstrative learning methods on early childhood gross motor development. Taken together, the literature suggests that demonstrative learning methods have significant potential in improving early childhood gross motor skills, prompting the need for further research to identify the most effective implementation strategies